2003
DOI: 10.1002/sdr.267
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and control of a simple dynamic system

Abstract: . His work focuses on dynamic and distributed decision making, and man-machine interface issues. AbstractThis study examined laypeople's understanding of a simple dynamic system, expressed in reasoning and strategies used by the subjects, and how it affected performance. Participants were 15 undergraduate psychology students, 4 male and 11 female; median age was 24 years, ranging from 21 to 31 years. The subjects' task was to establish equilibrium in a simple predatorand-prey system. A task analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 11 publications
3
51
0
Order By: Relevance
“…Finally, they detected the origin of the learning phase in CDCTs with only 12 learning trials (Experiment 1, 2) and with extended practice of 40 trials (Experiment 4). This is consistent with studies showing that self-reports, like think aloud protocols, accurately track control performance (e.g., Burns & Vollmeyer, 2002;Gonzalez et al, 2003;Gonzales & Quesada, 2003;Jensen & Brehmer, 2003). Overall, these findings are particularly hard to reconcile within an implicit learning account that claims knowledge is acquired incidentally and is unavailable to consciousness.…”
Section: What Kind Of Knowledge Is Learnt In Complex Skilled Control supporting
confidence: 76%
“…Finally, they detected the origin of the learning phase in CDCTs with only 12 learning trials (Experiment 1, 2) and with extended practice of 40 trials (Experiment 4). This is consistent with studies showing that self-reports, like think aloud protocols, accurately track control performance (e.g., Burns & Vollmeyer, 2002;Gonzalez et al, 2003;Gonzales & Quesada, 2003;Jensen & Brehmer, 2003). Overall, these findings are particularly hard to reconcile within an implicit learning account that claims knowledge is acquired incidentally and is unavailable to consciousness.…”
Section: What Kind Of Knowledge Is Learnt In Complex Skilled Control supporting
confidence: 76%
“…For example, in studies of CDC tasks, judgments of self-efficacy have used as an index of agency, and been shown to have powerful effects on causal knowledge (Jensen & Brehmer, 2003;Osman, 2008a). Osman (2008a) revealed that high judgments of selfefficacy in turn led to the successful identification of causal structures in the CDC task, and to better control performance, which in turn lead to further increases in self-efficacy.…”
Section: Agency and Causalitymentioning
confidence: 99%
“…We address many commonly cited reasons for poor performance in dynamic decision-making studies and stock-flow contexts (e.g., Atkins, Wood, & Rutgers, 2002;Booth Sweeney & Sterman, 2000;Jensen & Brehmer, 2003;Sterman & Booth Sweeney, 2007). Experiments 1-4 test whether information displays (Atkins et al, 2002), the cognitive burden of required calculations (Roch, Lane, & Samuelson, 2000), inadequate motivation, unfamiliar task context, or the inability to interpret or construct graphs (Ossimitz, 2002) contribute to SF failure.…”
Section: Introductionmentioning
confidence: 99%